Neurose visceral: estudo de um distúrbio urbano - Carvalho, Marcia Maria Rocha Alves de (1980)
Alonso Fernandes' phenornenological approach was the base of this study. The author tries to prove that has been a qualitative evolution in the way of discharging the exceeding stress, the anxiety flowing into the somatic. Better saying, today there's no more place to histery, demonstrative, theater like, needing a stage to work out. Today's life, impersonal, active and materialist, made out of use the mechanism that changes repressed anxiety into bodyly symbol. The praising of the young, the lack of space, the high aspiration level and a great amount of stress make understandable that man converges all the exceeding anxiety produced by city life, to his body. The present study asks about the existence of an specific pathology in the people that react that way. To verify that, 3 different groups with 30 people in each one, were used. They were divided in: health, with organic diseases and with psychosomatic diseases. Two kinds of instruments were applied with the aim of studying the personality profile of the sample: MPI Inventory and a questionnaire that comprises the life style, costumes, habits, income, education, etc. from the studied group. The basic hypothesis is that there is not a specific mental pathology in the psychosomatic patients and that things like little physical space, tne exagerate aspiration level, the self-image preocupation and the stress level are preponderant personality traces in people with psychosomatic diseases. It was verified with a good certitude margin the idea that the flight to the body is not a pathologic syndrome but a defense mechanism, a help to the individual obliged to survive under the tensions of our days. Beyond that, the apiration’s level answers incidence in the psychosomatic diseased group, proves that variable to be one of the big traits that propitiate the somatic via choice as an anxiety discharge form.